How do you solve

$x(x-4)-2=43$ ?

David Rojas
2022-01-23
Answered

How do you solve

$x(x-4)-2=43$ ?

You can still ask an expert for help

porekalahr

Answered 2022-01-24
Author has **10** answers

Step 1

$x(x-4)-2=43$

$x\times x-x\times 4-2=43$

${x}^{2}-4x-2-43=43-43$

${x}^{2}-4x-45=0$

$\mathrm{\Delta}={(-4)}^{2}-4\times 1\times (-45)$

$\mathrm{\Delta}=196$

$x=\frac{-b\pm \sqrt{\mathrm{\Delta}}}{2a}$

$x}_{1}=\frac{-(-4)-\sqrt{196}}{2$

$x}_{2}=\frac{-(-4)+\sqrt{196}}{2$

${x}_{1}=-5,\text{}{x}_{2}=9$

0 here's our answer!

0 here's our answer!

Mazzuranavf

Answered 2022-01-25
Author has **10** answers

Step 1

Expand the bracket

$x(x-4)-2=43\Rightarrow {x}^{2}-4x-2=43$

Subtract 43 from both sides

${x}^{2}-4x-45=0$

Factorise

$(x-9)(x+5)=0$

So$x=9$ or -5

Expand the bracket

Subtract 43 from both sides

Factorise

So

asked 2021-11-03

Write the equation of the quadratic function whose graph is a parabola containing the points $(10,72)$ , $(0,-3)$ , and $(-5,34.5)$ .

asked 2022-02-11

write the standard form of a quadratic equation with roots of -6 and 4

asked 2020-12-03

what polynomial can be added to ${x}^{2}+5x+1$ to get a sum of $4{x}^{2}-3$

asked 2022-04-19

Solving a quadratic equation with 3 parameters

$\frac{1}{a}\cdot ({x}^{2}-bx)+6a+5b=5x+\frac{6{b}^{2}}{a}$

asked 2022-04-06

Finding $\lambda$ such that ${\left(\mathrm{ln}({x}^{2}-2x+2)\right)}^{2}+\lambda \mathrm{ln}({x}^{2}-2x+2)+1>0\mathrm{\forall}x>1$

asked 2021-12-27

How do you expand $(x-y)}^{3$ ?

asked 2021-08-13

Prove that $-{3}^{4}\ne {(-3)}^{4}$